3D concrete printing of topological interlocking blocks - Tom Goertzen; Tobias Neef; Philipp Scheffler; Domen Macek; Viktor Mechtcherine; Alice C. Niemeyer (Materials & Design)
In this work the feasibility of combining the concept of topological interlocking assemblies (TIA) with 3D concrete printing is investigated. In TIA, blocks are arranged in a manner that, when kinematically constrained by a surrounding frame, all blocks in the entire assembly become immovable solely through the contact between neighbouring blocks, eliminating the need for binding materials. This study aims to investigate whether blocks for a TIA can be produced using 3D concrete printing. For this a method for path planning specially tailored for the manufacturing of TIA blocks, guaranteeing contact between blocks is introduced and three blocks that admit TIA are manufactured. For one block geometry, an assembly with 18 blocks in the form of a slab system is chosen and constructed for further experiments. The structural behaviour of this slab system composed of printed topological interlocking blocks is evaluated by both a finite element method analysis and experimental testing. The findings underscore the feasibility of integrating TIA with 3D concrete printing, highlighting potential applications in sustainable construction.